Employment status three years after percutaneous coronary intervention and predictors for being employed: A nationwide prospective cohort study. (June 2020) - Olsen, Siv JS; Schirmer, Henrik; Wilsgaard, Tom; Bønaa, Kaare H; Hanssen, Tove A
Background: Vocational support is recommended for patients in cardiac rehabilitation (CR), as returning to work is important in patients social readjusting after an acute coronary event. Information is lacking on whether CR leads to higher long-term employment after percutaneous coronary intervention (PCI). Aims: The aims of this study were to determine employment status three years after PCI, to compare employment status between CR participants and CR non-participants and to assess predictors for employment. Methods: We included first-time PCI patients from the NorStent trial, who were of working age (<63 years; n = 2488) at a three-year follow-up. Employment status and CR participation were assessed using a self-report questionnaire. Propensity score method was used in comparing employment status of CR participants and CR non-participants. Results: Seventy per cent of participants who were <60 years of age at the index event were employed at follow-up and CR participation had no effect on employment status. Being male, living with a partner and attaining higher levels of education were associated with a higher chance of being employed, while being older, prior cardiovascular morbidity and smoking status were associated with lower chance of being employed at follow-up. Conclusion: Because a significant number of working-age coronary heart disease patients are unemployed three years after coronary revascularization, updated incentives should be implemented to promote vocational support. Such programmes should focus on females, patients lacking higher education and patients who are living alone, as they are more likely to remain unemployed.